Effects of thermal radiation in a thermocapillarity thin film flow on an unsteady stretching sheet - Raziana Che Aziz; Ishak Hashim (2011)
This paper examined the effects of thermocapillarity and thermal radiation on the boundary layer flow and heat transfer in a thin film on an unsteady stretching sheet. The governing partial differential equations are reduced to ordinary differential equations by a similarity transformation and hence solved by using Homotopy Analysis Method. The effect of thermal radiation is considered in the energy equation and the variations of dimensionless surface temperature as well as the heat transfer characteristics with various values of Prandtl number, thermocapillarity number, radiation parameter are graphed and tabulated.(Abstract by authors)